Pembuatan Komik Metamorfosis Kupu-Kupu untuk Anak Sekolah Dasar Kelas Tinggi - Mifta, Mifta; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discussed about butterfly’s metamorphosis comic making for elementary school children of high class. The purpose of this paper is to describe the process of making a comic of metamorphosis of butterfly. The technique of collecting data in the preparation of this paper is observation of the literature by reading and studying ther source book, comics, metamorphosis of butterflies, and elementary school children of high class. Based on the stu88dy can be concluded the stages of comic making of metamorphosis of butterfly for elementary school children of high class as follow: (1) determine the topic or theme of the comic to be created, (2) collect all kinds of informations needed in making comic, (3) thinking about creating a comic figure or figure, (4) make a script of story that will be made comic, (5) create an image of a script that has been created, (6) giving balloons of conversation in the picture, (7) giving color to sketch or drawing that have been made,(8) take in the conversation text as well as the text in the column to explain the baground setting, (9) then scan the results of comic sheets that have been completed, (10) cut each existing panel and then neatly arranged, (11) the next, create a comic book cover with the desired creations. Stages of comic creation have been completed. Comics can be printed and ready to use.Keywords: comic, metamorphosis of butterflies.